Coordination of systems through numeraires - Garrido, Paulo (2015)
A paradigm for coordination of systems is proposed based on a controller with enough power to induce coordination among systems with respect to some goal.The power considered here is of organization dissolution or system deletion, conditional on the values of an exchangeable scalar criterion applied to the system by the controller. The criterion is called a numeraire because the paradigm was abstracted from economic systems based on money.One describes a method for the computer representation of producing systems based on string rewrite rules. Then, one studies the regulation problem for an abstract example of a coordinated system through a numeraire. First, one considers to define and enforce a nominal operation point; second, one studies the effects of disturbances and what can the controller do to minimize them.Although the example is simple, it shows instructive results and allows to consider several research lines.